The regeneration of the tail fin actinotrichia of carp (Cyprinus carpio, Linnaeus, 1758) under the action of naproxen - Böckelmann,PK. (2009)
A conglomerate of small, rigid, fusiform spicules known as actinotrichia sustains the edge of tail fins of teleost. After amputation, these structures show an extremely fast regenerative capacity. In this study we observed the effect of a nonsteroidal anti-inflammatory drug, naproxen, used in the treatment of degenerative articular diseases, during the process of actinotrichia regeneration. For this purpose, regenerating tissue from animals in contact with the drug was submitted to histochemical and ultrastructural analysis in comparison to tissue from animals under normal conditions, i.e., not in contact with the drug in question. Actinotrichia regeneration was similar in both animals, indicating that naproxen, at the dose used in the present study, did not interfere with actinotrichia synthesis during the regenerative process of the tail fin. This could be because naproxen did not influence the expression of the genes required for the regeneration process, such as the Sonic hedgehog (Shh) gene, which is involved in actinotrichia formation.